Handbook of Research on Computer-Enhanced Language Acquisition and Learning 2008
DOI: 10.4018/978-1-59904-895-6.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Grammar Animations and Cognition

Abstract: The present study is situated in the context of cognitive aspects of language processing as it focuses on the learning and teaching of grammar in various modes of presentation. The success of the programs developed for, and used in, the study is measured in terms of short- and long-term learner performances in the application of grammatical rules. Four groups of informants were formed to test four different combinations of the presented materials. The groups used either a cognitive/functional or traditional ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…It is, however, quite possible that dynamic aids will not always ensure greater L2 learning than static images (Boers et al, 2009). The advantage of dynamic visual input may be related to various factors such as developmental principles (Roche & Scheller, 2008) or the provision of additional verbal information (Niknejad & Rahbar, 2015). Students who fit the verbalizer profile, on the other hand, tend to learn L2 vocabulary better with a vocabulary list than with images (Sato & Burden, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is, however, quite possible that dynamic aids will not always ensure greater L2 learning than static images (Boers et al, 2009). The advantage of dynamic visual input may be related to various factors such as developmental principles (Roche & Scheller, 2008) or the provision of additional verbal information (Niknejad & Rahbar, 2015). Students who fit the verbalizer profile, on the other hand, tend to learn L2 vocabulary better with a vocabulary list than with images (Sato & Burden, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, in the case of the preposition over illustrated by the trajectory image in Figure 1, dynamic-image technology can easily display motion. Roche and Scheller (2008) also concluded that the dynamic images developed along cognitive principles bring positive learning effects.…”
Section: Applying the CL Framework To Dynamic L2 Learning Materialsmentioning
confidence: 95%
See 2 more Smart Citations
“…Recent metaphor awareness-raising approach studies have evaluated the efficacy of animated visualisation in teaching German grammar, such as motion verbs (Roche & Scheller, 2008), passive voice (Arnett et al, 2019), case systems (Gradel, 2016), modal verbs (Kanaplianik, 2016), and light verbs (Suñer & Roche, 2019); and in teaching English, such as vocabulary (Sato et al, 2021) and degrees of politeness (Takimoto, 2021). All studies compared the metaphor awareness-raising and non-metaphorical instructional approaches without a control group (Arnett et al, 2019;Gradel, 2016;Kanaplianik, 2016;Roche & Scheller, 2008;Sato et al, 2021;Suñer & Roche, 2019) The studies by Gradel (2016) and Suñer and Roche (2019) compared the animated metaphor awareness-raising approach and teacher-directed traditional teaching approach.…”
Section: Animated Visualisation In the Metaphor Awareness-raising App...mentioning
confidence: 99%